Relationship between predation by Podisus nigrispinus and developmental phase and density of its prey, Plutella xylostella - Vacari, Alessandra M. [UNESP]; De Bortoli, Sergio A. [UNESP]; Torres, Jorge B. (Wiley-Blackwell, 2012)
This study evaluated the predation by Podisus nigrispinus (Dallas) (Hemiptera: Pentatomidae) at various densities of larvae and pupae of the pest Plutella xylostella (L.) (Lepidoptera: Plutellidae). We tested predator behavior of female P. nigrispinus at six experimental densities (1, 5, 10, 15, 20, or 25 prey items in a 1-l transparent plastic container, replicated 15 times for each density) of both the fourth instar and pupae of P. xylostella. The number of prey consumed was monitored every 15 min for 12 h and was subsequently monitored at 24 h. Podisus nigrispinus females were weighed before and after the experiments to determine the effect of different densities of prey on their weight gain. Female predators had a Type-II functional response, with attack rate estimated at 1.387 and 0.260 and a handling time of 0.091 and 0.183 h-1 for larvae and pupae, respectively. Podisus nigrispinus consumed on average 10.9 larvae or 5.5 pupae in 24 h. Despite the similarity of the response type, P. nigrispinus preferred to feed on larvae, rather than on pupae.
Keywords: Asopinae; Biological control; functional response; preference test; Hemiptera; Pentatomidae; Lepidoptera; Plutellidae